2013
DOI: 10.1161/circgenetics.112.963140
|View full text |Cite
|
Sign up to set email alerts
|

Causal Relevance of Blood Lipid Fractions in the Development of Carotid Atherosclerosis

Abstract: Background— Carotid intima–media thickness (CIMT), a subclinical measure of atherosclerosis, is associated with risk of coronary heart disease events. Statins reduce progression of CIMT and coronary heart disease risk in proportion to the reduction in low-density lipoprotein cholesterol. However, interventions targeting triglycerides (TGs) or high-density lipoprotein cholesterol (HDL-C) have produced inconsistent effects on CIMT and coronary heart disease risk, making it uncertain whether such agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…Additional evidence against the role of HDL in CVD risk has come from genetic studies, designed to examine the associations of LDL, HDL and TG with CVD risk [29,30]. Early studies showed that rare mutations that encode LCAT (lecithin cholesterol acyl transferase) and ABCA1 (ATP-binding cassette transporter, also known as cholesterol efflux regulatory protein (CERP)), which profoundly reduce HDL levels, were inconsistently associated with CVD risk [29].…”
Section: Discussionmentioning
confidence: 99%
“…Additional evidence against the role of HDL in CVD risk has come from genetic studies, designed to examine the associations of LDL, HDL and TG with CVD risk [29,30]. Early studies showed that rare mutations that encode LCAT (lecithin cholesterol acyl transferase) and ABCA1 (ATP-binding cassette transporter, also known as cholesterol efflux regulatory protein (CERP)), which profoundly reduce HDL levels, were inconsistently associated with CVD risk [29].…”
Section: Discussionmentioning
confidence: 99%
“…One study investigated the LDLR locus and found that individuals carrying protective alleles in the LDLR gene have a reduced lifelong exposure to LDL-C of 0.19 mmol/L per T allele compared with C allele homozygotes, translating into a 21–23% lower risk of MI 20. By using weighted genetic scores, subsequent MR studies have expanded the investigation to include multiple LDL-C associated single nucleotide polymorphisms (SNPs) and all have confirmed this association, concluding that LDL-C is causal in the CHD pathway 10 21 22. The conclusions of these MR studies further support the notion that lowering LDL-C results in successful prevention of CHD.…”
Section: Mendelian Randomisation: An Emerging Methodologymentioning
confidence: 99%
“…They concluded that HDL-C plasma levels were not causal for MI risk. Two other studies using an HDL-C genetic score also found that HDL-C levels were not causal in the onset of CHD 21 22. A study by Holmes et al included two genetic scores in their analysis of HDL-C, one which included SNPs with pleiotropic effects on LDL-C and TGs and another which limited its genetic score to SNPs that associated exclusively with HDL-C.…”
Section: Mendelian Randomisation: An Emerging Methodologymentioning
confidence: 99%
“…In an analysis performed in 2 prospective cohorts, Whitehall II (WHII; n=5059) and the British Women's Heart and Health Study (BWHHS; n=3414), individuals in the top versus bottom quintile of an LDL-C GRS consisting of 23 SNPs had a higher risk of CAD (WHII: OR=1.43; BWHHS: OR=1.31). 87 After adjusting for LDL-C levels, this association was completely attenuated in WHII but not in BWHHS. The value of a GRS for CAD risk prediction beyond conventional risk factors has improved beyond previous studies considering a small number of risk variants 88,89 beyond those related to plasma lipid traits to more recent analyses incorporating a more comprehensive list of recently identified CAD loci.…”
Section: Utility Of a Genetic Risk Score For Risk Assessment And Treamentioning
confidence: 98%